HOW TO CREATE AN PERFECT NEW NATURE LEARNING TEXT FOR DISTANCE STUDY - Skrypnyk, Maryna Ivanivna; Kravchynska, Tetiana Serhiivna; Volynets, Nataliia Petrivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The present article deals with the research on educational text libraries, exploration on the creation of texts focused on the use of different platforms of semiotic systems, developments in design (graphic, web) and visualization became the basis for the analysis of creolized educational texts. Approaches to the classification of such texts are researched, the most popular E-resources for the creation of educational texts of a new nature are outlined.